IMPROVING STUDENTS’ WRITING ABILITY THROUGH CUE CARDS TECHNIQUE - Fenny Thresia (Premise: Journal of English Education and Applied Linguistics, 2017)
This research is a qualitative research with two variables. The classroom action research is conducted at phisics study program of Muhammadiyah University of Metro. The subject of this research is first semester students of physics study program. The number of the students is 22. The objective of this research was to know how cue cards technique improve the students’ writing ability in descriptive text. The researcher choose one class because they have problem in writing ability. This research was conducted in two cycles. Each cycle consisted of planning, acting, observing and reflecting. The data were collected from test (pre test and post test), observation. The result of this research can be seen from the average score of pre test (before treatment) was 61,86, in cycle 1 was 70,90 and in post test cycle 2 was 78. That was involved in upgrading maximally. It implied that cue cards technique can improve the students writing ability in descriptive text. In other words, the class had fulfilled criteria success of standard students competency from the school.It was supported by the observation of the students. From the result of the discussion, the researcher concludes that in this research there is an improvement student writing ability in descriptive text using cue cards technique at the students of physics academic year 2015/2016.Key Words : Descriptive Text, Writing Ability, Cue Cards Technique